Diseño de un sistema de servicio de telefonía pública con tecnología de voz sobre IP para aplicaciones locales - Livise Aguilar, Richard Enrique (2017)
The methodological study of the problematic of the public telephony service in a determined locality of the city of Lima is carried out; defining the problem, in order to achieve the improvement of service delivery, in terms of coverage and access with a economies of scale approach. The research objectives are established, in relation to the variables of the problem; as well as its importance, delimitation and justification. The compilation and analysis of the information related to the provision of public telephony services at national and local level, is carried out; as well as the technical information of the infrastructure that is generally used for the implementation of fixed and mobile telephony services. In order to have a sufficiently documented theoretical basis for the presentation of a proposed solution to the problem of coverage and access to public telephony services, with a economies of scale approach in the framework of the implementation of social integration policies, conducted by the Executive, in the district of El Agustino, province and department of Lima. A quantitative, descriptive and correlational research is carried out; It is established as a study population the people of both sexes from 17 to 65 years old with residence in the housing cooperative Huancayo 2nd stage of the district of El Agustino, province and department of Lima. and a sample of 256 people is established. A population consultation process is executed through the application of an opinion survey and the hardware and software required for the implementation of the proposed solution to the problem of public telephony service provision are evaluated and selected. The conclusions and recommendations for the implementation of the proposed solution to the problem of public telephony service provision are presented and a tentative budget is prepared for the installation of the necessary equipment.